2021
DOI: 10.1088/1742-6596/2070/1/012141
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of pre-trained transfer learning models for the classification of the rolling bearing faults

Abstract: Nowadays, artificial intelligence techniques are getting popular in modern industry to diagnose the rolling bearing faults (RBFs). The RBFs occur in rotating machinery and these are common in every manufacturing industry. The diagnosis of the RBFs is highly needed to reduce the financial and production losses. Therefore, various artificial intelligence techniques such as machine and deep learning have been developed to diagnose the RBFs in the rotating machines. But, the performance of these techniques has suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Pre-trained models(vgg19,vgg16) have been employed for TL in this study, and the final three layers of the model have been fine-tuned to categorize ten different types of defects. When training a network, transfer learning is a simpler method than starting from scratch with a deep learning model [19]. In general, transfer learning is an effective deep learning technique that enables models to use information from datasets or prior tasks to enhance performance on new tasks.…”
Section: B Pre-trained Model and Transfer Learningmentioning
confidence: 99%
“…Pre-trained models(vgg19,vgg16) have been employed for TL in this study, and the final three layers of the model have been fine-tuned to categorize ten different types of defects. When training a network, transfer learning is a simpler method than starting from scratch with a deep learning model [19]. In general, transfer learning is an effective deep learning technique that enables models to use information from datasets or prior tasks to enhance performance on new tasks.…”
Section: B Pre-trained Model and Transfer Learningmentioning
confidence: 99%
“…The most popular models were AlexNet, VGG, Xception, Inception, MobileNet, DenseNet, ResNet, GoogleLeNet, and YOLOs. In (Abu et al, 2022;Sharma et al, 2021;Zhao, 2017), all suggested considering fine-tuning several hyperparameters (feature map, filter size, activation function, pool size, optimiser, learning rate, batch size, epoch, dropout rate, loss function, and evaluation metric) of the pre-trained model.…”
Section: Transfer Learningmentioning
confidence: 99%